Associations between agronomic and bread-making quality traits in wheat: location and crop-year effects - Bornhofen, Elesandro; Woyann, Leomar Guilherme; Bozi, Antonio Henrique; Stoco, Matheus Giovani; Marchioro, Volmir Sergio; Benin, Giovani (Científica, 2018)
The present study aimed to evaluate the associations between agronomic and bread-making quality traits in wheat under different growing environments. Nineteen Brazilian wheat cultivars were evaluated at six locations (Cascavel-PR, Castro-PR, Guarapuava-PR, Palotina-PR, Abelardo Luz-SC, and Não-Me-Toque-RS) during five years (2007 to 2011). The direction and magnitude of the associations between agronomic and bread-making quality traits were strongly dependent on the test location and year of evaluation. This study discusses the implications of choosing test locations on bread-making quality traits and for breeding purposes, with emphasis on indirect selection.